Empowering Women in the Workplace: Analyzing Japanese Women's Employment Trends in the 1950s and Their Implications for Leadership and Team Dynamics in Sports - Zhoulian Xu, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The 1950s marked significant advancements in women's employment in Japan, characterized by an increase in workforce participation, expanded employment opportunities, and the implementation of laws aimed at protecting female workers. However, challenges persisted, including a concentration in support roles, limited opportunities for promotion, low wages, career interruptions, and workplace norms that encouraged marriage, childbirth, and eventual withdrawal from the workforce. These issues were shaped by a workplace environment that restricted women's upward mobility and societal attitudes that reinforced traditional gender roles. Women's employment decisions during this period were also influenced by their career awareness, which was primarily driven by economic needs rather than aspirations for long-term professional development. The root cause of these dynamics lay in the deeply ingrained perception of gender-based division of labor in Japanese society, perpetuated through school education and cultural norms. These findings hold relevance for sports psychology by highlighting the parallels between workplace and team environments. Understanding the historical and cultural factors that influence gender dynamics provides insights into fostering inclusivity, leadership development, and resilience in sports teams and organizations, promoting a more equitable and empowering environment for women in both professional and athletic contexts.